Sub-Regional Biophysical and Monetary Evaluation of Ecosystem Services: An Experimental Spatial Planning Implementation - Anna Richiedei; Marialaura Giuliani; Michele Pezzagno (Land)
Preserving soil is crucial for addressing the key challenges of the new millennium, like climate change and biodiversity loss. Spatial planning plays a pivotal role in stopping soil consumption and degradation, thereby safeguarding soils that provide valuable ecosystem services. With the advent of the System of Environmental-Economic Accounting by the UN, countries are developing a shared protocol for the biophysical and monetary quantification of ecosystem services. However, downscaling efforts are necessary and must be conditioned by the national context, policies, economic dynamics, and data availability. Therefore, this research proposes a soil quality assessment methodology based on its ecosystem value at the sub-regional level in northern Italy, building upon national guidelines. This study includes modeling and mapping outputs involving six ecosystem services through eight biophysical indicators and the monetary quantification of these services. Both assessments have been conducted over two time periods to highlight the impacts of land cover transformation.